PENGARUH LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BELAJAR SISWA DI MAN BALAI SELASA KECAMATAN RANAH PESISIR KABUPATEN PESISIR SELATAN - -, Fitria - (Pendidikan Geografi, 2014)
Research for this aims to look at the School of Physical and Environmental Effects of Social Environment Student Motivation At MAN Balai Selasa Ranah Pesisir District of Pesisir Selatan District. The research is a descriptive correlational statistical analysis. The population in this study were all students of class X MAN Balai Selasa Ranah Pesisir District of Pesisir Selatan District. Sampling technique in this study using stratified random sampling technique, totaling 88 people. The data of the physical environment, social environment and the motivation to learn is done by distributing questionnaires. Based on the results of the study show that: (1) The test instrument consisted of research on test data validity and reliability testing. Test the validity of the data concluded that the data is valid because r count> rtabel (0.361> 0.213). Test reliability of the data concluded that the data is reliable because r count> rtabel (2.011> 0.213); (2) The average score of 71.5 with the physical environment category of Self; (3) The average score of 76.9 with a social environment both categories; (4) The average score of 73.8 with a social environment both categories. (5) There is a significant relationship between the physical environment on student motivation, namely (1.76> 1.67); (6) There is a significant relationship between the social environment on student motivation, namely (2.33> 1.67); (7) There is a significant relationship between physical and social environment on student motivation, namely (4.08> 1.67). Based on the findings it can be concluded that the physical environment and social environment influence on Student Motivation At MAN Balai Selasa Ranah Pesisir District of Pesisir Selatan District. .